Maternal region of origin and Small for gestational age: a cross-sectional analysis of Victorian perinatal data - Sarah Grundy; Patricia Lee; Kirsten Small; Faruk Ahmed (BMC, 2021)
Abstract Background Being born small for gestational age is a strong predictor of the short- and long-term health of the neonate, child, and adult. Variation in the rates of small for gestational age have been identified across population groups in high income countries, including Australia. Understanding the factors contributing to this variation may assist clinicians to reduce the morbidity and mortality associated with being born small. Victoria, in addition to New South Wales, accounts for the largest proportion of net overseas migration and births in Australia. The aim of this research was to analyse how migration was associated with small for gestational age in Victoria. Methods This was a cross sectional population health study of singleton births in Victoria from 2009 to 2018 (n = 708,475). The prevalence of being born small for gestational age (SGA; <10th centile) was determined for maternal region of origin groups. Multivariate logistic regression analysis was used to analyse the association between maternal region of origin and SGA. Results Maternal region of origin was an independent risk factor for SGA in Victoria (p < .001), with a prevalence of SGA for migrant women of 11.3% (n = 27,815) and 7.3% for Australian born women (n = 33,749). Women from the Americas (aOR1.24, 95%CI:1.14 to 1.36), North Africa, North East Africa, and the Middle East (aOR1.57, 95%CI:1.52 to 1.63); Southern Central Asia (aOR2.58, 95%CI:2.50 to 2.66); South East Asia (aOR2.02, 95%CI: 1.95 to 2.01); and sub-Saharan Africa (aOR1.80, 95%CI:1.69 to 1.92) were more likely to birth an SGA child in comparison to women born in Australia. Conclusions Victorian woman's region of origin was an independent risk factor for SGA. Variation in the rates of SGA between maternal regions of origin suggests additional factors such as a woman's pre-migration exposures, the context of the migration journey, settlement conditions and social environment post migration might impact the potential for SGA. These findings highlight the importance of intergenerational improvements to the wellbeing of migrant women and their children. Further research to identify modifiable elements that contribute to birthweight differences across population groups would help enable appropriate healthcare responses aimed at reducing the rate of being SGA.